Quantification of different silicon fractions in broadleaf and conifer forests of northern China and consequent implications for biogeochemical Si cycling - Yang, Xiaomin; Song, Zhaoliang; Yu, Changxun; Ding, Fan (Geoderma, 2020)
•Terrestrial biogeochemical Si cycle is strongly influenced by labile Si fractions.•The contribution made by non-crystalline Si fraction to total Si was 1.51–2.31%.•Biogenic amorphous Si contributed more to the Si cycle in the broadleaf forests.•Pedogenic amorphous Si contributed more to the Si cycle in the conifer forests.•Soil organic matter, pH, and plant communities can affect the Si transformation. The terrestrial biogeochemical silicon (Si) cycle significantly contributes to maintaining the functions and sustainability of terrestrial ecosystems. Over the short term, the biogeochemical Si cycle can be strongly influenced by dissolved Si, organic bound Si, Si adsorbed to pedogenic oxides/hydroxides, and biogenic and pedogenic amorphous Si. However, quantitative studies about these relatively soluble Si fractions are rare. In this study, we quantified different Si fractions in the 0–10 cm, 10–20 cm, 20–30 cm, 30–40 cm and 40–50 cm soil layers of broadleaf forests (Betula forest and Quercus forest) and conifer forests (Larix forest and Pinus forest) in northern China using a sequential chemical extraction scheme optimized for these Si fractions. The results showed that the total Si (Sit) in the soil layers consisted of 97.7–98.5% crystalline Si (Sicry) and 1.5–2.3% non-crystalline Si (Sinoncry) fractions. Within the Sinoncry fraction, the proportions of dissolved Si (Sidis), organic matter bound Si (Siorg), pedogenic oxides/hydroxides chemisorbed Si (Sisorb), and amorphous Si (Siamor) were 3.4–6.7%, 5.5–8.9%, 6.3–8.5%, and 77.7–84.8%, respectively. Although the Sidis fraction was the least abundant component, it is at the center of the interconversion processes among the different Sinoncry fractions. The Siamor fraction was the largest component of Sinoncry and was composed of 37.7–71.9% biogenic amorphous Si (Sibio-amor) and 28.1–62.3% pedogenic amorphous Si (Siped-amor). Our study indicated that i) Siped-amor fraction is more easily influenced by soil pH comparing to Sibio-amor fraction; ii) the Sibio-amor fraction contributes more to the biogeochemical Si cycle in broadleaf forests, whereas the Siped-amor fraction contributes more in conifer forests; and iii) soil pH, soil organic matter, and plant community differences can influence the vertical distribution of the different Sinoncry fractions and thus affect the multiple transformation processes among these Si fractions in studied forests.